2017
DOI: 10.3892/etm.2017.5076
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sirt1 in a rat model of high‑fat diet‑induced non‑alcoholic fatty liver disease: Comparison of Gegen Qinlian decoction and resveratrol

Abstract: The present study aimed to explore the mechanism of action of Gegen Qinlian decoction (GGQLD) in experimental non-alcoholic fatty liver disease (NAFLD). A total of 30 rats were randomly divided into five groups: The chow, model, high- and low-dose GGQLD (GGQLD-H and GGQLD-L, respectively) and resveratrol (Resl) groups, and were treated with saline, GGQLD and Resl when a model of high-fat diet (HFD)-induced NAFLD was established. Blood lipid and liver enzymes were detected following treatment for 8 weeks and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Chinese herbal medicine (CHM) has been traditionally used in China and other Asian countries for thousands of years. A specific and basic feature of Chinese medicine is the use of formulas containing several herbs (herbal cocktail) to ameliorate abnormal symptoms associated with a particular disease[8]. Dachaihu decoction (DCHD), a classical formula from the Treatise on Febrile Disease , is one of the well-known traditional Chinese medicines and consists of: Chinese thorowax root ( Bupleurum chinensis DC .…”
Section: Introductionmentioning
confidence: 99%
“…Chinese herbal medicine (CHM) has been traditionally used in China and other Asian countries for thousands of years. A specific and basic feature of Chinese medicine is the use of formulas containing several herbs (herbal cocktail) to ameliorate abnormal symptoms associated with a particular disease[8]. Dachaihu decoction (DCHD), a classical formula from the Treatise on Febrile Disease , is one of the well-known traditional Chinese medicines and consists of: Chinese thorowax root ( Bupleurum chinensis DC .…”
Section: Introductionmentioning
confidence: 99%
“…Liver is a central metabolic organ that regulates essential functions of lipid homeostasis. SIRT-1 plays an important role in TG metabolism in the liver, and increasing evidences suggest an inverse correlation between SIRT-1 levels and non-alcoholic fatty liver disease (NAFLD) ( Mariani et al, 2015 ; Guo et al, 2017 ). Liver specific deletion of SIRT-1 contributes to increased inflammation, endoplasmic reticulum stress and hepatic steatosis ( Purushotham et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…A unique and basic feature of CHM is the use of multicomponent herbal formulas to ameliorate various abnormalities and diseases. For example, formulas like Linggui Zhugan [24], Yinchenhao [25], and Gegen Qinlian decoction (GGQLD) [26] have been used to treat NAFLD. GGQLD, a well-known traditional CHM from the Treatise on Febrile Diseases, consists of Kudzu root , Rhizoma coptidis, Scutellaria baicalensis Georgi, and Glycyrrhizae Radix and is widely used to clinically treat NASH.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GGQLD, which is under conventional dose, has been regarded as a kind of safe and potential treatment in treating NASH until now. In our previous studies, we found that GGQLD has an anti-inflammatory effect [27, 28], which could regulate lipid metabolism disorders and improve liver histology of the rats during NAFLD pathogenesis [26, 29]. In addition, the active components of GGQLD, including baicalin, glabridin, and berberine, have been shown to alleviate inflammation and oxidative stress in vivo and in vitro [30, 31].…”
Section: Introductionmentioning
confidence: 99%